Solar photovoltaic system Fast Acting MPPT Algorithm for Soft Switching Interleaved Boost Converter (International Journal of Food and Nutritional Sciences, 2021)
Conventional DC-DC converters operate at high frequencies, which causes noise, high output voltage ripple, and high switching voltage stress. These issues reduce the effectiveness of traditional boost converters and cause low voltage gain. Soft switching modified interleaved boost converter with twin linked inductors is utilized to solve the aforementioned issues. By sharing the input current, the primary windings of two linked inductors are parallel connected to reduce current ripple at the input side. The stress on the switch voltage and output voltage ripple are reduced by output capacitors connected in series. Additionally, the secondary of two coupled inductors is coupled in series.